Pollution or Crime: The Effect of Driving Restrictions on Criminal Activity - Paul E. Carrillo; Andrea López; Arun S. Malik (Inter-American Development Bank (IDB), 2016)
Driving restriction programs have been implemented in many cities around the world to alleviate pollution and congestion problems. Enforcement of such programs is costly and can potentially displace policing resources used for crime prevention and crime detection. Hence, driving restrictions may increase crime. To test this hypothesis, this paper exploits both temporal and spatial variation in the implementation of Quito, Ecuador's Pico y Placa program and evaluates its effect on crime. Both difference-in-difference and spatial regression discontinuity estimates provide credible evidence that driving restrictions can increase crime rates.
hdl:11319/7731
Keywords: C20; Q52; R28; R48; 330; Crime; Difference-in-Differences; Regression discontinuity; Crime displacement